Aplicação de autoria de código para melhoria de processo de atendimento de uma empresa de desenvolvimento de software - Perin, Jociano (2019)
Process modeling aims to standardize the activities of a process and outline it in a clear and consistent manner, avoiding any doubt to stakeholders as to what should be done within a particular business. This approach is widely used in organizations that aim to fully understand their own processes and continually improve them. This paper proposes to model a process for the help desk department of a software developer company. Additionally, it is proposed to improve the attendant assignment process to perform a service, using the code authorship technique. This technique aims to assign the best attendant to perform a new service. The selection of the best attendant is based on histories provided by the company, where is located the attendant who in the shortest time solved that problem or similar. The new process model has been successfully applied to the company, and the results indicate that the use of automation where there are bottlenecks in a process can not only optimize it but increase the quality of service provided.